Evaluation of Dental Age in Nepali Children using Demirjian’s 7-Teeth Teeth Method - Nyachhyon, Rinky (Orthodontic Journal of Nepal, 2017)
Introduction: Age estimation can be based on tooth formation stages seen on the radiographs. Demirjian’s method is widely used to assess age of individuals with developing dentition. There are not many documented studies of age estimation amongst Nepali population. Objective: To assess the applicability of Demirjian’s method for dental age estimation in Nepali children. Materials & Method: The sample of the study consisted of 186 subjects between 7-16 years of age. Dental age estimation was based on Demirjian’s method and scored by a single observer. Result: The mean and mean differences in chronological and dental ages were calculated, which revealed the overestimation in age groups of 7 and 9 years, whereas there were underestimations in other age groups. The mean differences in age groups 12-16 were highly significant (p-Value <0.05) whereas the mean difference in age groups 7-11 years were not statistically significant. Conclusion: Since there is underestimation range from 0.5 years to 1.23 years, the standards of dental maturity described by Demirjian may not be suitable for Nepali children.